THE SYMBIOTIC RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND CREATIVITY - Bakıxanova Khavarkhanum Agamehdi (International Journal of Innovative Technologies in Social Science, 2025)
Although emotional intelligence and creativity may seem like two different factors that are unrelated to each other, research has shown that they are interconnected and that this connection plays a crucial role in the comprehensive development of human potential. In this article, we will examine the symbiotic relationship between emotional intelligence and creativity, that is, how they mutually develop each other.Aim and methods: The aim of this research was to examine relation between emotional intelligence and creativity of students. For this purpose, firstly various literature sources were analyzed to answer the main research questions. Survey material and assessment tool were chosen to analyze the relation between two factors.Measuring the direction and strength of the interaction between emotional intelligence and creativity, identifying specific psychological processes that explain how these two constructs improve each other, comparing how relationships change in different circumstances (age, culture, profession), and developing recommendations for training and education programs based on the results obtained are some of the important issues to be resolved today.Conclusion: The definition of emotional intelligence as a person's ability to understand, manage, and express his or her own and others' emotions reveals its direct connection with the creative process. Creativity is a multidimensional factor that manifests itself not only in the field of art, but also in problem solving and everyday decision-making. Research shows that creative processes deepen emotional understanding and lead to the development of self-awareness and empathy.Although the existing literature suggests a certain relationship between emotional intelligence and creativity, the mechanisms of symbiotic interaction between them, the dynamics of this relationship, and its consequences have not been systematically investigated. In particular, there is no unified model that explains the relationship between the components of emotional intelligence (self-awareness, self-regulation, motivation, empathy, social skills) and the stages of creativity (preparation, incubation, insight, verification). In addition, there is a need to conduct research on the dynamic relationship between the components of emotional intelligence and the stages of creativity, the role of emotional activity in the preparatory stage, the importance of emotional tolerance during the incubation period, the relationship between emotional depth and creativity during enlightenment, the impact of the development of a creative personality on the development of emotional intelligence, and the limiting and enhancing factors between them.Due to the lack of a single model and insufficient literature, we considered it more appropriate to conduct the study in the direction of determining the symbiotic relationship between emotional intelligence and creative potential. The additional section at the end of the article reflects the emotional intelligence and creative potential indicators of each of the respondents. When analyzing the results, it becomes clear that there is no direct significant relationship between emotional intelligence and creative potential. It is clear from the study that while all students with high creative potential have very high emotional intelligence indicators, not all students with high emotional intelligence have high creative potential.The article focuses not on the one-way relationship between emotional intelligence and creativity, but on the mutual influence. This focus places the research within a deep, comprehensive, and at the same time constrained framework, which we hope will allow for a scientifically efficient and consequential study.